How can a traffic light properly work if it is always green? The paradox of CK2 signaling. (4th July 2021) - Borgo, Christian; D'Amore, Claudio; Cesaro, Luca; Sarno, Stefania; Pinna, Lorenzo A.; Ruzzene, Maria; Salvi, Mauro
Abstract: CK2 is a constitutively active protein kinase that assuring a constant level of phosphorylation to its numerous substrates supports many of the most important biological functions. Nevertheless, its activity has to be controlled and adjusted in order to cope with the varying needs of a cell, and several examples of a fine-tune regulation of its activity have been described. More importantly, aberrant regulation of this enzyme may have pathological consequences, e.g. in cancer, chronic inflammation, neurodegeneration, and viral infection. Our review aims at summarizing our current knowledge about CK2 regulation. In the first part, we have considered the most important stimuli shown to affect protein kinase CK2 activity/expression. In the second part, we focus on the molecular mechanisms by which CK2 can be regulated, discussing controversial aspects and future perspectives.